A medical cyber-physical system utilizing the bayes algorithm for post-diagnosis patient supervision - Mizanur, Rahman; Talha, Sarwar; Ahmed, Zahiduddin; Miah, M. Saef Ullah; Bhowmik, Abhijit; Nusrat, Fahmeda; Junaida, Sulaiman (AIUB Office of Research and Publication, 2024)
Among several basic human needs, medical treatment is one of the most prominent. However, since there need to be more doctors, nurses, and other medical facilities in many places, medical cyber-physical systems are quickly becoming a competitive alternative. One important use of these systems is for observation after a diagnosis. Instead of active observation by a caregiver, this can be easily done using various monitoring systems. However, most of the existing systems for this application are inflexible and need to consider the current challenges. On the other hand, these problems can be solved by intelligent and adaptive systems, which is now possible thanks to the growth of relevant technology, especially healthcare 4.0. Therefore, this article proposes an adaptive system based on the Bayes algorithm for performing medical interventions on patients, leading to a reduction in the dependence on caregivers, particularly in the post-diagnosis scenario.